The emergence of 'Piecemeal Pedagogy': a case study of selected South African grade 4-7 English and social studies teachers' positions and practices toward learning and teaching support materials - Koornhof, Hannchen Elizabeth (My University, 2017)
This thesis is located in the area of the enactment of learning materials. It examined examines the thinking and practices related to Learning and Teaching Support Materials (LTSM) of a small sample of South African teachers in Gauteng, across different school sectors, who worked in the Intermediate Phase and taught English and/or Social Sciences. Most international research, conducted in relatively homogeneous environments showed how teachers’ enactment with of learning materials always varied (from teacher to teacher) and was variable (within the practices of a single teacher). The A gap in international research exists in the narrow interpretation of LTSM and assumptions that learners in a class had similar language facility and backgrounds. In this thesis, learning materials were of necessity interpreted more widely than textbooks, and the research also spanned diverse social, linguistic and economic teaching environments for comparative purposes. The policy context of South Africa comprises multiple curriculum changes and a socio-political context of vast inequalities between schools. In a conceptual framework, devised for this research, the intersections in the teacher-learner-LTSM classroom triad were examined. This framework targets three central areas:hones in on how the affordances of materials were used, how coherence was achieved in lessons and across the curriculum, and how each of the triad’s elements participated contributed to in the overall impact of LTSM delivery and reception. The main findings from 26 classroom observation sessions, 18 interviews and an analysis of textual artefacts (LTSM) are that textbooks were rarely used and that teachers' discourses about LTSM are of two kinds: a classroom management discourse (using a variety of materials can combat boredom / arouse interest)and a teacher professional identity discourse (teachers as materials developers). After doing 26 classroom observations, conducting 18 interviews with teachers, as well as textbook and worksheet analysis, main findings were that textbooks were rarely used in classrooms across all teaching sectors, based on two separate discourses. In the first discourse, teachers used a variety of materials to combat learners’ boredom and distraction, as a means to achieve classroom management. In the second discourse, teachers felt that professionalism and the production of their own materials were linked. The result was that learners in all schools received a piecemeal exposure to the curriculum, through visual media and teachers’ handouts in the form of worksheets. There were differences in how the teachers enacted these LTSM, indicating differences in teaching philosophies: Differences in how the teachers enacted these LTSM indicated teaching philosophies: some teachers aimed at making learners participants in the learning process, whereas others wanted to control the transmission process. Worksheets were mainly limited in content and made few demands on the learners and teachers. In this small-scale research study, the limited exposure that learners received to reading texts and related writing opportunities were linked to the kind of LTSM that were used and the teachers’ enactment of these materials. Many of the teachers acknowledged that this situation has had a pronounced impact on learners’ abilities to interpret texts and to express themselves adequately in class and during assessments. However, according to the teachers interviewed, the limited English proficiency of some learners, the density of the curriculum, the lack of confidence of some teachers and their sometimes difficult working conditions, all militate against changes to their practices.However, according to teachers, language constraints, the curriculum’s density, the lack of teachers’ confidence and sometimes difficult working conditions militated against any change in practice
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Wits School of Education, Faculty of Humanities, University of the Witwatersrand, Johannesburg 2017
Keywords: Teaching--Aids and devices; English language--Study and teaching (Elementary)